PEG2000-PLA-based nanoscale polymeric micelles reduce paclitaxel-related toxicity in beagle dogs - Lu, Jun; Han, Bo; Zhang, Bo; Zou, Benkun; Hu, Minjuan; Liu, Hongyu; Zhou, Chao; Qian, Fangfei; Wang, Shuyuan; Zhang, Yanwei; Lou, Yuqing; Chu, Tianqing; et al. (Journal of controlled release, 2023)
Nanoplatform-based drug delivery plays an important role in clinical practice. Polymeric micellar (Pm) nanocarriers have been demonstrated to reduce the toxicity of paclitaxel in rats and non-small cell lung cancer (NSCLC) patients. However, the underlying toxicological profile needs to be further illustrated. Here, we used beagles as study subjects and sought to further observe the toxicological profile of polymeric micellar paclitaxel (Pm-Pac) via acute toxicity tests and short-term and long-term toxicity tests. The results from the acute toxicity test indicated that the lethal dose of Pm-Pac in beagles was 20–30 mg/kg, and the acute toxicity-targeted organs were the digestive system and immuno-haematopoietic system. The short-term toxicity test suggested that paclitaxel-induced toxicity (peripheral neuropathy toxicity, haemopoietic toxicity, heart system toxicity, and so on) in beagles can be reduced when paclitaxel is delivered via the Pm delivery system. The long-term toxicity test suggested that Pm-Pac can reduce haemopoietic toxicity in beagles. Collectively, this study provides novel insight into the toxicological profile of Pm-Pac in healthy beagles and provides a potential basis for promising clinical combination strategies in the future. [Display omitted]